A design of nano‐optical Yagi‐Uda antenna with high forward directivity. Issue 4 (April 2017) - Chen, Xiaolin; Yu, Wenhai; Yue, Wencheng; Yao, Peijun; Liu, Wen
ABSTRACT: Optical antennas, acting as converters between propagating and localized fields, can be employed in near‐field microscopy and high‐resolution biomedical sensors. Utilizing the multi‐sphere dyadic Green's function, we propose a nonperiodic optical nanoantenna made of a metallic nanoparticles dimer chain. Our numeric results show that the antenna has a high forward directivity and vanishing backward directivity simultaneously even without a reflector. Our work reveals the role of nonperiodicity in design of optical Yagi‐Uda nanoantenna. © 2017 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:786–789, 2017